Metabolism of Indole-3-Acetic Acid: III. Identification of Metabolites Isolated from Crown Gall Callus Tissue - Feung, Chao-Shieung (1976)
The metabolism of labeled indole-3-acetic acid (IAA-2-(14)C) was investigated in Parthenocissus tricuspidata crown gall callus tissue. After 48 hours incubation, 85 to 90% of the supplied IAA was taken up by the tissue, and of that taken up, about 45% was conjugated with five amino acids. The conjugates found were aspartic and glutamic acid (minor ones) as well as glycine, alanine, and valine (major ones). The last four are being reported for the first time as metabolites of IAA. These conjugates were identified through their chromatographic properties, hydrolysis products, and their mass spectra. The possible significance of these amino acid conjugates is discussed.